Obtención de microestructuras de carbono para la remoción de metales pesados en aguas contaminadas. - Mena Pástor, Johny Adrián (2022)
Worldwide water contamination by heavy metáis can derive from anthropogenic activities or from natural sources. Therefore, it is necessary to implement new alternatives for the remediation of water resources. The present research project aims to obtain carbón microstructures from glucose, urea and acrylic acid for the removal of heavy metáis in contaminated water. For this purpose, carbón structures were synthesized from different monomers varying the conditions of time (16-48h) and temperature (180-190°C), then the microstructures obtained with higher yield were characterized by scanning electrón microscopy and finally their ability to remove copper (II) was studied. Additionally, a completely randomized statistical analysis was performed. As a result of the hydrothermal synthesis different carbón microstructures were obtained with yield percentages for glucose at 180° for 24h glucose of 98.90%R, followed by glucose + urea at 180° for 24h glucose + urea with 19.66%R, glucose + urea + acrylic acid at 180° for 24h glucose + urea + acrylic acid with 9.91%R. The analysis of the micrographs obtained from the 6 samples analyzed showed different morphologies and particle sizes, in the case of the glucose samples, they are spherical with sizes between 2-20 pm, in the case of GU they have an irregular fragment type shape and finally the glucose + urea + acrylic acid samples have an irregular fragment type shape, but these are in layers. For the removal of heavy metáis, a concentration of copper (II) sulfate at 30 ppm was used, which was nrixed with the carbón microstructures, stirred for 3 hours and stabilized at pH, and then filtered and analyzed in the spectrophotometer. The sample that obtained the highest removal capacity was G with 45.86%R, followed by glucose + urea + acrylic acid 28.54%R and finally the glucose + urea sample with 13.20%R removal. With these results we can affirm that, if it is possible to remove heavy metáis from water by rneans of carbón microstructures from glucose, urea and acrylic acid, this innovative rnethod will contribute to future research on the presence of heavy metáis in contaminated water.